Penetapan Kadar Asam Klorogenat dan Aktivitas Antioksidan Ekstrak NADES dari Biji Kopi Hijau Robusta (Coffea canephora) Menggunakan Metode MAE dan UAE sebagai Bahan Baku Kosmetik - Alishlah, Tanfidz; Nuri, Nuri; Dianasari, Dewi; Rahman Hakim, Arif (Journal of Pharmaceutical and Sciences, 2025)
Antioxidants are essential for protecting skin cells from free radicals, causing oxidative damage, and supporting human skin’s health. Natural antioxidants are abundant in plants, particularly in Robusta green coffee beans (Coffea canephora), which are rich in chlorogenic acid (CA), a key contributor to antioxidant properties. Efficient extraction methods are necessary to obtain these bioactives effectively. Advanced extraction technology, such as Ultrasound-Assisted Extraction (UAE) and Microwave-Assisted Extraction (MAE), enhances mass transfer and reduces processing time compared to conventional methods. This study quantified chlorogenic acid using Thin Layer Chromatography-Densitometry (TLC-densitometry) and evaluated the antioxidant activity using the DPPH method of NADES (betaine–triethylene glycol) liquid extracts from Robusta coffee green beans extracted via UAE and MAE. Chlorogenic acid concentration of MAE (3.64 mg CA/g extract ± 0.06) was higher than that of UAE (2.69 mg CA/g extract ± 0.04). The antioxidant activity (IC₅₀) values were 3266.66 μg/mL ± 67.97 (UAE) and 2598.05 μg/mL ± 29.42 (MAE), indicating higher efficiency for MAE. When expressed as chlorogenic acid equivalents in NADES extracts, IC₅₀ values were 9.04 μg/mL ± 0.13 (UAE) and 9.44 μg/mL ± 0.07 (MAE). NADES-MAE could be a promising method to acquire raw materials with high antioxidant activity, especially for cosmetic formulation.